Internal Audit Function And Independence Of The Board Of Commissioners Towards The Company - Nurmawati Mambuhu; Irwan Moridu (Proceeding of The International Conference on Business and Economics, 2023)
As payment for conducting the audit, the auditor will impose audit fees on the entity being audited. A number of variables, such as the task's complexity, the level of skill needed to complete it, the pay scale for knowledge development programs, and other professional considerations, affect the fees that auditors charge to do audits. The purpose of this study is to determine the effects of audit fees for the Indonesia Stock Exchange's banking subsector between 2021 and 2022 on corporate risk, internal audit function, and board of commissioners independence. The study's population comprises firms that have been indexed on the Indonesia Stock Exchange for a certain timeframe, spanning from 2021 to 2022. Purposive selection was used to pick data from 100 banking subsectors that were listed on the Indonesia Stock Exchange for the study sample. In this study, quantitative analysis is used. The Eviews 12 software was used to conduct the analysis. The findings of the partial test indicate that the audit fee is influenced by the risk of the internal audit function and the independence of the board of commissioners, but that company risk and board independence have no effect on the audit fee.